Prism processing method, prism and camera module

CN118184160BActive Publication Date: 2026-10-27KUNSHAN Q TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410185759.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-19
Publication Date
2026-10-27
Estimated Expiration
2044-02-19

AI Technical Summary

Technical Problem

[0004]本申请实施例通过提供一种棱镜加工方法、棱镜和摄像模组,解决了现有技术中棱镜开槽使得棱镜强度降低,在对棱镜进行机械类测试时,棱镜容易断裂的技术问题,实现了提高开槽棱镜的强度的技术效果

Benefits of technology

[0034]本实施例将设置有目标槽的待处理棱镜浸泡在目标酸性溶液中,通过目标酸性溶液对待处理棱镜的外表面进行均匀腐蚀,进而可以逐渐减小目标槽内的裂纹深度,进而提高棱镜的强度,提高棱镜在机械类测试中的通过率,提高良品率,降低废品率,进而降低生产成本。在较优情况下,还可以通过控制浸泡时长或者目标酸性溶液的浓度,完全消除目标槽内的裂纹,进而可以进一步提高棱镜的强度,提高棱镜在机械类测试中的通过率,提高良品率,降低废品率,进而降低生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118184160B_ABST
    Figure CN118184160B_ABST
Patent Text Reader

Abstract

The application discloses a prism processing method, a prism and a camera module, and relates to the technical field of prism processing, and aims at improving the strength of the prism, improving the pass rate of the prism in mechanical tests, improving the yield, reducing the waste rate, and reducing the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical technology, and in particular to a prism processing method, a prism, and a camera module. Background Technology

[0002] With the increasing demand for telephoto shooting, periscope lenses have emerged. Periscope lenses can achieve telephoto shooting by increasing the light path through the refraction of light using mirrors or prisms without increasing the thickness of electronic devices (such as mobile phones and tablets).

[0003] However, periscope lenses are prone to creating abnormal lighting and shadows when shooting in strong light, resulting in lower image quality. To address this, a light-blocking mechanism can be installed by slotting the prism at a specific location to block interfering light. However, slotting the prism reduces its strength, making it prone to breakage during mechanical testing. Therefore, improving the strength of slotted prisms is a pressing issue that needs to be addressed. Summary of the Invention

[0004] This application provides a prism processing method, a prism, and a camera module, which solves the technical problem in the prior art that slotting the prism reduces its strength and makes it prone to breakage during mechanical testing, thus achieving the technical effect of improving the strength of the slotted prism.

[0005] In a first aspect, this application provides a prism processing method, the method comprising:

[0006] A prism to be processed is provided, and a target groove is provided on the prism to be processed;

[0007] The prism to be treated is immersed in the target acidic solution for a preset time to obtain a pretreated prism with a corrosion layer formed on its surface.

[0008] Remove the pretreated prism, remove the corrosion layer, and obtain the target prism.

[0009] Furthermore, a prism to be processed is provided, including:

[0010] Provide the original prism;

[0011] Based on the distribution area of ​​interfering light in the original prism, determine the target grooving parameters corresponding to the grooving of the original prism; the target grooving parameters include the shape, size and location of the groove.

[0012] The grooving particle size and grooving feed rate for each of the N grinding operations are determined based on the target grooving parameters; where N is a positive integer greater than or equal to 1.

[0013] The original prism is grooved according to the corresponding grooving particle size and grooving feed amount for each grinding, to obtain the prism to be processed.

[0014] Furthermore, the methods for determining the preset duration include:

[0015] Determine the crack depth of the prism to be treated in the region where the target groove is located;

[0016] The preset duration is determined based on the corrosive intensity of the target acidic solution and the crack depth.

[0017] Further, the corrosion layer is removed, including:

[0018] Grind the surface of the target groove of the prism to be processed;

[0019] The outer surface of the prism to be processed is finely ground and polished.

[0020] Furthermore, after obtaining the target prism, the method also includes:

[0021] Detect whether the penetration rate of the target prism in the target slot exceeds a preset threshold;

[0022] When the penetration rate of the target prism in the target slot exceeds a preset threshold, the outer surface of the target prism is ground until the penetration rate of the target prism in the target slot is less than the preset threshold.

[0023] Furthermore, after obtaining the target prism, the method also includes:

[0024] A light-shielding material is coated inside the target groove of the target prism to obtain a semi-finished prism;

[0025] The target type of colloid is filled into the target groove of the semi-finished prism to obtain the finished prism;

[0026] Among them, the target type of colloid is a heat-curing colloid; the viscosity of the target type of colloid is 5000 mPa.s-25000 mPa.s.

[0027] Furthermore, the thrust of the target prism is greater than 20 kgf.

[0028] Furthermore, the target acidic solution is any one of hydrofluoric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0029] Furthermore, the concentration of hydrofluoric acid is 20%-60%.

[0030] Furthermore, the prism to be processed is made of glass.

[0031] Secondly, this application provides a prism, including a prism obtained by a prism processing method as provided in the first aspect.

[0032] Thirdly, this application provides a lens module, including a prism obtained by a prism processing method as provided in the first aspect.

[0033] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages:

[0034] In this embodiment, the prism to be treated, with a target groove, is immersed in a target acidic solution. The acidic solution uniformly corrodes the outer surface of the prism, gradually reducing the crack depth within the target groove. This improves the prism's strength, increases its pass rate in mechanical tests, increases the yield rate, reduces the scrap rate, and ultimately lowers production costs. In a preferred embodiment, by controlling the immersion time or the concentration of the target acidic solution, cracks within the target groove can be completely eliminated, further enhancing the prism's strength, improving its pass rate in mechanical tests, increasing the yield rate, reducing the scrap rate, and ultimately lowering production costs. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0036] Figure 1 This is a longitudinal sectional view of the prism with a slot at the bottom;

[0037] Figure 2 A top view of a prism with slots on both sides;

[0038] Figure 3 For application Figure 1 A schematic diagram of the camera module architecture of the prism shown;

[0039] Figure 4 This is a schematic diagram illustrating the principle of mechanical testing.

[0040] Figure 5 for Figure 1 A schematic diagram showing the distribution of cracks within the prism groove;

[0041] Figure 6 This is a flowchart illustrating a prism processing method provided in this embodiment;

[0042] Figure 7 Yes Figure 1 A longitudinal sectional view of the bottom groove after it has been filled with colloid;

[0043] Figure 8 This is a flowchart illustrating the processing method for the target groove provided in this embodiment;

[0044] Figure 9A schematic diagram of the optical path through which some of the interfering light is transmitted within the original prism;

[0045] Figure 10 To and Figure 8 A flowchart illustrating the adapted processing procedure.

[0046] Figure label:

[0047] 1-Pride to be processed, 2-Target groove, 3-Light-shielding material, 4-Lens assembly, 5-Pride holder, 6-Photosensitive chip, 7-Thrust fixture, 8-Push head, 9-Colloid, 10-Original prism, 11-Crack. Detailed Implementation

[0048] This application provides a prism processing method that solves the technical problem in the prior art where prism grooving reduces prism strength and makes prisms prone to breakage during mechanical testing.

[0049] The technical solution of this application embodiment is to solve the above-mentioned technical problems, and the general idea is as follows:

[0050] A prism processing method includes: providing a prism 1 to be processed, the prism 1 having a target groove 2; immersing the prism 1 in a target acidic solution for a preset time to obtain a pre-treated prism with an corrosion layer formed on its surface; removing the pre-treated prism, removing the corrosion layer, and obtaining the target prism.

[0051] In this embodiment, the prism 1 to be treated, with the target groove 2 provided, is immersed in a target acidic solution. The target acidic solution uniformly corrodes the outer surface of the prism 1, thereby gradually reducing the crack depth within the target groove 2, thus increasing the prism's strength, improving its pass rate in mechanical tests, increasing the yield rate, reducing the scrap rate, and ultimately lowering production costs. In a preferred embodiment, by controlling the immersion time or the concentration of the target acidic solution, the crack 11 within the target groove 2 can be completely eliminated, further improving the prism's strength, increasing its pass rate in mechanical tests, improving the yield rate, reducing the scrap rate, and ultimately lowering production costs.

[0052] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.

[0053] First, it should be clarified that the term "and / or" in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this article generally indicates that the preceding and following related objects have an "or" relationship.

[0054] To meet the demand for large-aperture telephoto camera modules in small, thin smart terminal devices, prisms are usually set inside the camera module. Prisms can fold the light path, thereby increasing the light path between the lens assembly and the imaging chip, thus extending the light path and enabling telephoto shooting.

[0055] While prisms can extend the optical path, they can also increase the amount of interference light entering from various assembly gaps and other areas within the camera module. This interference light, after entering the prism, is projected onto the imaging chip, causing glare and resulting in ghosting, halos, and other abnormal light and shadow effects on the image, thus affecting image quality.

[0056] The above problems can be solved by slotting specific parts of the prism (such as the bottom and / or sides) and coating the slots with a light-shielding material. The slotted structure on the prism can limit stray light from entering the prism to a certain extent and block interference light entering the optical path folding prism, thereby reducing the impact of interference light on image quality.

[0057] For example, such as Figure 1 and Figure 2 The diagram shown is a structural schematic of a trapezoidal prism, in which... Figure 1 This is a longitudinal sectional view of the prism with a slot at the bottom. Figure 2 This is a top view of the prism with slots on both sides. In actual operation, only the slots on the two sides can be cut. Figure 2 You can cut a groove on one side of the groove, or you can cut grooves on both sides at the same time. Figure 1 and Figure 2 The slot positions can be combined, meaning that slots can be made at the bottom and sides of the prism simultaneously to block interfering light at different locations.

[0058] Will Figure 1 The prism shown is applied to the camera module to obtain the following result: Figure 3 The camera module shown has a trapezoidal prism housed in a prism holder 5, with the trapezoidal prism and prism holder 5 fitting together. The lens assembly 4 (including a motor and other driving components) Figure 3 (The motor and other driving components are not shown in the image) and the photosensitive chip 6 are located on the same side of the trapezoidal prism. Figure 3 As shown by the gray arrow, light enters from the lens assembly 4, undergoes a light path reversal in the trapezoidal prism, and finally enters the photosensitive chip 6 to achieve telephoto imaging. Figure 3 The bottom of the prism has a groove, the inner surface of which is coated with a light-shielding material. Figure 3 (Not shown in the image), it can block interfering light within the height range of the slot to reduce the impact of interfering light on the imaging quality and improve the imaging quality.

[0059] However, mechanical testing of the slotted prisms revealed a significant decrease in strength, making them prone to breakage and resulting in a high scrap rate and increased production costs. For example, ... Figure 4 As shown, Figure 4 This is a schematic diagram illustrating the principle of mechanical testing. Figure 1 The prism shown was subjected to a thrust test, which involved placing the prism in the thrust fixture 7 with the slotted part facing down, and then applying force from top to bottom with the pusher head 8. The two sides of the prism to be processed (also referred to as the slotted prism in this embodiment) were blocked by the thrust fixture 7, causing the prism to be processed to be subjected to force. After the test, the average thrust of the prism to be processed was 15.5 kgf, which did not meet the minimum thrust requirement of 20 kgf for the prism. Therefore, the prism to be processed was very easy to break during mechanical testing, resulting in a high scrap rate.

[0060] Observing the slotted prism under a microscope or high magnification reveals that the slotted surface is rough and contains deeper micro-cracks 11, such as... Figure 5 As shown, Figure 5 A schematic diagram of microcrack 11 (surface roughness not shown). Figure 5 (As shown in the figure). Due to the presence of roughness and micro-cracks 11, the strength of the slotted prism is significantly reduced. For example, the maximum depth of the target slot 2 in the slotted prism is 2 mm, the location of crack 11 is 2.0 mm-2.1 mm, and the crack depth is about 0.1 mm.

[0061] To address the issue of prisms being prone to breakage after slotting, this embodiment provides, for example... Figure 6 The prism processing method shown includes steps S61-S63.

[0062] Step S61: Provide a prism to be processed 1, which has a target groove 2.

[0063] Step S62: Immerse the prism 1 to be treated in the target acidic solution for a preset time to obtain a pretreated prism with a corrosion layer formed on its surface.

[0064] Step S63: Remove the pre-treated prism, remove the corrosion layer, and obtain the target prism.

[0065] The prism to be processed 1 refers to a prism with slots for blocking interfering light. The target slot 2 includes all the slots on the prism to be processed 1 for blocking interfering light.

[0066] The target acidic solution is any one of hydrofluoric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0067] It is important to note that the prism 1 to be processed is made of glass, not plastic. Glass is chemically composed of silicon dioxide (SiO2). Silicon dioxide is chemically stable and does not react with common acids. Plastic, on the other hand, reacts relatively violently with most acids, easily leading to its complete dissolution. Therefore, the prism 1 to be processed in this embodiment cannot be a plastic prism.

[0068] Hydrofluoric acid reacts with silicon dioxide to produce gaseous silicon tetrafluoride. See the chemical reaction equation below for details:

[0069] SiO₂ + 4HF = SiF₄↑ + 2H₂O

[0070] Concentrated phosphoric acid (or pyrophosphoric acid) can corrode silica at high temperatures to produce heteropoly acids, as shown in the following chemical reaction formula:

[0071] SiO2 + 2H3PO4 (conc.) = SiP2O7 + 3H2O

[0072] Typically, when hydrofluoric acid is used as the target acidic solution, its concentration can range from 20% to 60%, with approximately 40% being the optimal choice. Using a 40% concentration of hydrofluoric acid to etch the prism 1 ensures a relatively mild reaction process while maintaining corrosion efficiency. When using concentrations below 40%, the closer the concentration is to 20%, the lower the corrosion efficiency, but the more controllable the corrosion process, reducing the risk of over-corrosion and other negative consequences. When using concentrations above 40%, the closer the concentration is to 60%, the higher the corrosion efficiency, but the lower the controllability of the corrosion process, making it more prone to over-corrosion and other negative consequences. Therefore, in actual operation, the concentration of hydrofluoric acid can be adjusted according to the required corrosion efficiency and controllability.

[0073] Table 1 below shows the standard specifications for various components in the hydrofluoric acid solution during the experiment, as well as the content of each component in the hydrofluoric acid solution used. Using the hydrofluoric acid solution shown in Table 1 can make the prism's strength reach over 20 kgf.

[0074] Table 1

[0075] Content (HF), % ≥40.0 41.7 Residue on ignition (as sulfate), % ≤0.002 0.001 Chloride (Cl), % ≤0.001 <0.001 <![CDATA[Sulfate and sulfite (calculated as SO4), %]]> ≤0.002 <0.002 <![CDATA[Phosphate (PO4), %]]> ≤0.0002 <0.0002 <![CDATA[Fluorosilicate (SiF6), %]]> ≤0.04 <0.04 Iron (Fe), % ≤0.0001 <0.0001 Heavy metals (as Pb), % ≤0.0005 <0.0005

[0076] The method for determining the preset duration includes steps S621-S622.

[0077] Step S621: Determine the crack depth of the prism 1 to be treated in the region where the target groove 2 is located;

[0078] Step S622: Determine the preset duration based on the corrosion intensity and crack depth of the target acidic solution.

[0079] Prisms are typically grooved using mechanical machining, resulting in surface roughness. This roughness, along with deeper cracks (11) visible under a microscope or high magnification, can be observed. Since the cracks (11) are deeper than the surface roughness, their depth is usually determined through estimation.

[0080] The crack depth is determined by measuring the crack 11 within the prism 1 under treatment using a microscope or high-power microscope. Corrosion intensity is generally proportional to the concentration of the target acidic solution; therefore, the concentration of the target acidic solution can be used to characterize the corrosion intensity. The preset treatment time is determined by combining the corrosion intensity and the crack depth.

[0081] Alternatively, a sample prism (made of the same material as the prism to be treated 1) can be etched using target acid solutions of different concentrations. The etching depth corresponding to different concentrations of target acid solutions at different durations can be recorded, and the etching depth can be used to characterize the etching intensity. By comparing the crack depth with the etching depth corresponding to different concentrations of target acid solutions at different durations, the target concentration of the target acid solution and the target duration can be determined. The target duration is used as the preset duration, and then the prism to be treated 1 is etched using the target concentration of target acid solution for the preset duration. The preset duration can be 15 minutes, 30 minutes, 40 minutes, etc., and can be set according to the actual situation.

[0082] After the prism 1 to be treated is etched with the target acidic solution, the state of the etched layer surface is uncontrollable. Therefore, the etched layer needs to be treated, that is, the etched layer on the surface of the prism 1 to be treated needs to be removed, which may include steps S631-S632.

[0083] Step S631: Roughly grind the surface of the target groove 2 of the prism 1 to be processed;

[0084] Step S632: Fine grinding and polishing are performed on the outer surface of the prism 1 to be processed.

[0085] Since the target groove 2 has a certain depth, the inner surface of the target groove 2 needs to be coarsely ground by a CNC machine tool to remove the corrosion layer. The coarse grinding particle size can be about 1000 mesh.

[0086] After coarse grinding of the inner surface of target groove 2, fine grinding and polishing can be performed on the inner surface of target groove 2, as well as on the remaining outer surfaces (mainly planes) of the prism 1 to be treated. When fine grinding and polishing the remaining outer surfaces of the prism 1 to be treated, multiple prisms 1 to be treated can be finely ground and polished simultaneously, thereby improving the efficiency of corrosion layer removal. The particle size for fine grinding can be 1000-1500 mesh, and the particle size for polishing can reach 1500-3000 mesh. Polishing can be achieved using cerium oxide polishing skin and zirconium oxide polishing skin. By coarsely grinding, finely grinding, and polishing the prism 1 to be treated after immersion in an acidic solution, the target prism is obtained, ensuring that the outer surface of the target prism remains relatively smooth and improving the consistency of the outer surface.

[0087] After obtaining the target prism, it is also possible to detect whether the penetration rate of the target prism in the target slot 2 exceeds a preset threshold. When the penetration rate of the target prism in the target slot 2 exceeds the preset threshold, the outer surface of the target prism is ground to reduce the penetration rate until the penetration rate of the target prism in the target slot 2 is less than the preset threshold.

[0088] The transmittance of target slot 2 refers to the ratio of the incident light to the emitted light after a beam of light enters one side of target slot 2 from the incident surface of the prism and exits from the other side. The transmittance of the target slot is generally required to be less than 0.5%.

[0089] For example, if the maximum depth of the target groove 2 in the prism 1 to be treated is 2 mm, and the depth of crack 11 is 2.1 mm, then the crack depth is 0.1 mm. In this case, the prism 1 to be treated can be immersed in the target acidic solution to dissolve its surface, increasing the overall depth of the target groove 2 to 2.05 mm, thus reducing the crack depth to 0.05 mm. Alternatively, by extending the immersion time, the overall depth of the target groove 2 can be increased to 2.15 mm, thereby completely eliminating crack 11 within the target groove 2. Figure 4 The mechanical testing principle shown applies mechanical testing to the obtained target prism. The thrust of the target prism can be greater than 20 kgf, thus meeting the thrust requirements of the prism.

[0090] In summary, this embodiment involves immersing the prism 1, which has a target groove 2, in a target acidic solution. The target acidic solution uniformly corrodes the outer surface of the prism 1, gradually reducing the crack depth within the target groove 2. This improves the prism's strength, increases its pass rate in mechanical tests, increases the yield rate, reduces the scrap rate, and ultimately lowers production costs. In a preferred embodiment, by controlling the immersion time or the concentration of the target acidic solution, cracks 11 within the target groove 2 can be completely eliminated, further enhancing the prism's strength, improving its pass rate in mechanical tests, increasing the yield rate, reducing the scrap rate, and ultimately lowering production costs.

[0091] Furthermore, based on the above-mentioned method of obtaining the target prism by immersing the prism 1 in an acidic solution, a light-shielding material 3 can be coated inside the target groove 2 of the target prism to obtain a semi-finished prism. The light-shielding material 3 is usually black and can be made of materials such as ink. By coating with the light-shielding material 3, interfering light inside the prism can be blocked, thereby reducing ghosting in the image and improving the image quality of the prism.

[0092] After obtaining the semi-finished prism, the target type of colloid 9 can be filled into the target groove 2 of the semi-finished prism to obtain the finished prism. For example... Figure 7 The diagram shown is a schematic of a finished prism after the semi-finished prism has been filled with adhesive in the groove.

[0093] The space ratio of the colloid 9 filled into the target groove 2 to the target groove 2 needs to be less than or equal to 100%. This means that the colloid 9 in the target groove 2 cannot overflow, avoiding negative impacts such as misalignment and excessive gaps caused by overflowing colloid 9 on the assembly of the prism body and the prism support 5. Furthermore, the space ratio of the colloid 9 filled into the target groove 2 to the target groove 2 needs to be greater than or equal to 25%. This means that the amount of colloid 9 filled cannot be too small; too little colloid 9 filling the target groove 2 will not provide sufficient strength for the prism and will not effectively reduce the risk of breakage of the slotted prism. In other words, the space ratio of the colloid 9 filled into the target groove 2 to the target groove 2 needs to be distributed between 25% and 100% (including the endpoint values ​​of 25% and 100%) to ensure sufficient strength for the prism. For example, the space ratio of the colloid 9 filled into the target groove 2 to the target groove 2 can be 50% or 70%.

[0094] Colloid 9 needs to be elastic, with an elastic range of 500 MPa to 1500 MPa. Colloid 9 is relatively moderate within this elastic range, neither too hard nor too soft. If it is too hard, it will be brittle and have poor impact resistance; if it is too soft, it will not be able to increase sufficient strength.

[0095] The target type of colloid 9 is a heat-curing colloid. Heat-curing colloids have a smaller volume shrinkage rate before and after curing, which can reduce the impact of the volume change of colloid 9 on the stress of the slotted prism, thus ensuring that the PV value of the slotted prism does not change significantly.

[0096] UV adhesive is generally not chosen as the filler 9 in the target groove 2 in this embodiment because it shrinks significantly before and after curing. For example, a UV adhesive that is 1 mm in diameter before curing will shrink to 0.9 mm after curing. In contrast, a heat-curing adhesive that is 1 mm in diameter before curing may shrink to 0.95 mm-0.98 mm after curing. Therefore, the shrinkage rate of heat-curing adhesives is much smaller, which reduces the impact of changes in the volume of colloid 9 on the stress of the slotted prism, thus ensuring that the PV value of the slotted prism does not change significantly.

[0097] The viscosity of the target type of colloid 9 is 5000 mPa·s-25000 mPa·s. This viscosity range is moderate, so that the colloid 9 will not flow onto the surface of the prism due to too low a viscosity, nor will the colloid 9 have too poor flowability due to too high a viscosity, thus reducing the uniformity of the distribution of the colloid 9 in the tank.

[0098] In this embodiment, by filling the target groove 2 of the semi-finished prism with colloid 9, the adhesive force of colloid 9 is used to connect the inner surface of the target groove 2 with colloid 9. When mechanical tests are performed on the finished prism after filling with colloid 9, the thrust can be overcome not only by the prism itself, but also by the colloid 9 in the target groove 2 and its connection with the inner surface of the target groove 2. This can improve the strength of the slotted prism, increase the pass rate of the slotted prism in the thrust test, reduce the risk of prism breakage, reduce the scrap rate, and reduce production costs.

[0099] In addition, the filling of the target type of colloid 9 into the target groove 2 of the semi-finished prism is usually done using a dispensing needle. A suitable dispensing needle of appropriate size can be selected based on the actual width of the target groove 2. The maximum outer diameter of the dispensing needle is smaller than the actual width to avoid needle collision when inserting into the target groove 2. Typically, the maximum outer diameter of the dispensing needle is at least 0.3 mm smaller than the actual width of the target groove 2. While ensuring that the maximum outer diameter of the dispensing needle is at least 0.3 mm smaller than the actual width of the target groove 2, a needle with a larger inner diameter can be selected to increase the speed of the dispensing process and thus improve dispensing efficiency.

[0100] After determining the target dispensing needle, before filling the target type of colloid 9 into the target groove 2 of the semi-finished prism, it is necessary to degas the target type of colloid 9. Typically, a centrifuge is used to process the target type of colloid 9, using a high rotation speed (e.g., 2000 rpm) to remove air bubbles from the target type of colloid 9.

[0101] After the target type of colloid 9 is degassed, the target type of colloid 9 is filled into the target groove 2 of the semi-finished prism using a target dispensing needle. The air pressure of the target dispensing needle should remain stable during the filling process, and the air pressure fluctuation should be less than a preset threshold (e.g., 0.01 MPa). This can ensure the uniformity and consistency of the colloid 9 injected into the target groove 2, and can also improve the strength of the target prism to a certain extent.

[0102] The target type of adhesive 9 can be filled into the target groove 2 of the semi-finished prism by either dispensing or spraying. Specifically, the target type of adhesive 9 can be filled into the target groove 2 of the semi-finished prism by dispensing or spraying. Typically, filling a prism by dispensing takes 10-20 seconds, while filling it by spraying takes only about 2 seconds. Therefore, spraying is more efficient. In practical applications, spraying is the preferred method for filling the target groove 2.

[0103] The target type of colloid 9 is filled into the target groove 2 of the semi-finished prism. This can be done in one continuous filling or in at least two separate fillings. Typically, when using the one-time filling method, the colloid is filled in one go using a dispensing needle along the extension direction of the target groove 2, and then cured by heating. This method is more efficient.

[0104] Compared to single-pass filling, multiple-pass filling is less efficient. For example, when filling in two stages, the first pass requires heating to cure the injected adhesive 9, followed by a second pass, and finally another heating process. This is time-consuming and inefficient. Therefore, a single-pass filling method is typically chosen to fill the target type of adhesive 9 into the target groove 2 of the semi-finished prism.

[0105] After filling the prism with adhesive as described above, a finished prism is obtained. The finished prism can then undergo mechanical strength testing, for example, by using... Figure 4 The test principle shown determines the actual strength of the finished prism, which can provide such finished modules for camera modules with higher strength requirements.

[0106] This embodiment provides six different colloids for filling the target groove 2, as shown in Table 2, which are the compositions of Glue 1, Glue 2, Glue 3, Glue 4, Glue 5, and Glue 6, respectively. The strength of the finished module obtained after filling with different colloids varies. The appropriate colloid 9 can be selected based on the actual strength requirements of the camera module to form a finished module that meets the corresponding strength requirements. This embodiment will not elaborate on this aspect.

[0107] Table 2

[0108]

[0109]

[0110] use Figure 4 The mechanical testing principle shown applies to the finished prism. The thrust of the finished prism can typically exceed 40 kgf, far exceeding the basic thrust requirement of 20 kgf. In actual operation, the strength of the prism can be comprehensively improved by combining acidic solution corrosion and adhesive filling methods, depending on the specific circumstances.

[0111] In addition, the processing method for the target groove 2 of the prism 1 to be processed includes steps S81-S83, such as... Figure 8 As shown.

[0112] Step S81: Provide the original prism 10, and determine the target grooving parameters corresponding to the grooving of the original prism 10 based on the distribution area of ​​the interfering light in the original prism 10; the target grooving parameters include the shape, size and location of the grooving.

[0113] Step S82: Determine the grooving particle size and grooving feed rate for each of the N grinding operations based on the target grooving parameters; where N is a positive integer greater than or equal to 1.

[0114] Step S83: Groove the original prism 10 according to the grooving particle size and grooving feed amount corresponding to each grinding to obtain the prism 1 to be processed.

[0115] The interference light in the original prism 10 may vary depending on the prism; this embodiment only uses... Figure 9 The interference light shown is part of the light. Figure 9 The example of the light path transmitted within the original prism 10 (using the gray lines in the image) will be used for illustration. Figure 9 The interference light in the original prism 10 has a certain height and area relative to the bottom of the original prism 10. Based on the distribution area of ​​the interference light, the shape, size and area of ​​the slot to be cut at the bottom of the original prism 10 can be determined.

[0116] Grooving is typically performed using a grinding wheel, which can be done with precision engraving equipment at a feed rate of 30-50 mm / min. A smaller value for N results in higher grooving efficiency, while a larger value for N results in lower efficiency. Generally, a single grooving process can be used to obtain the prism to be processed (1), i.e., N=1, followed by etching with an acidic solution to obtain the target prism.

[0117] In addition, when N is greater than 1 and the grinding particle size is small each time (e.g., less than 1000), the inner surface roughness of the groove on the prism is large. It can be etched with an acidic solution to reduce or eliminate roughness and cracks.

[0118] When N exceeds 1 and the grinding particle size gradually increases each time, the inner surface roughness of the groove on the prism is small, and crack 11 will be basically eliminated. Therefore, it is not necessary to use acidic solution to etch it. Of course, acidic solution can also be used to further improve the surface quality of the prism according to the actual situation.

[0119] The process where N exceeds 1 and the grinding particle size gradually increases with each grinding step is as follows:

[0120] The grinding particle size and grooving feed rate are determined based on the target grooving parameters. If the grooving particle size is too small, the grooving time will be longer, affecting the grooving efficiency. If the grooving particle size is too large, the roughness inside the groove will be high, affecting the prism quality. Therefore, it is necessary to select an appropriate grooving particle size. The grooving feed rate is usually related to the grooving particle size; the larger the grooving particle size, the larger the grooving feed rate, and the smaller the grooving particle size, the smaller the grooving feed rate.

[0121] To ensure both grooving efficiency and quality, the prism can be grooved using a multi-stage grinding process. The number of grinding stages, N, is typically greater than 1. While more grinding stages result in lower surface roughness after grooving, they also significantly reduce grinding efficiency. Therefore, in practice, the number of grinding stages must be determined by considering both grinding efficiency and surface roughness; generally, 2-4 stages are suitable.

[0122] It is important to note that during N grinding processes, the grooving particle size for the next grinding process is always larger than that for the previous grinding process, which causes the surface roughness to gradually decrease after grinding.

[0123] After determining the grooving particle size and grooving feed rate for each grinding cycle, the original prism 10 is grooved according to the corresponding grooving particle size and grooving feed rate for each grinding cycle to obtain the prism 1 to be processed. During each grinding cycle, the grinding area can be cleaned, lubricated, and cooled. After each grinding cycle, the grinding area also needs to be cleaned before starting the next grinding cycle.

[0124] In this embodiment, the original prism 10 is grooved by multiple grinding processes to obtain a groove with a certain surface roughness, typically 0.05-1 μm. A light-shielding material is then coated into the groove with this roughness, resulting in relatively good adhesion and ensuring good bonding between the material and the groove surface, thus better blocking interfering light.

[0125] This embodiment combines Figure 10 The process of slotting a prism is described using an example:

[0126] The interference light of a certain original prism 10 is distributed within a range of 2.1 mm from the bottom of the prism. Therefore, it can be determined that the shape of the slot is arched, the maximum depth is 2.1 mm, and the slot position is the bottom.

[0127] Grooving is achieved through a four-stage grinding process:

[0128] First grinding Q1: The grooving particle size is 450 mesh, and the grooving feed rate is 0.2mm. The first grinding needs to create a rough shape. During the grinding process, cleaning, lubrication, and cooling are required. After the first grinding, the grinding area needs to be cleaned to avoid residual particles affecting the roughness of the next grinding.

[0129] Second grinding Q2: The grooving particle size is 1000 mesh, and the grooving feed rate is 0.07mm; the second grinding requires fine-tuning of the shape, and cleaning, lubrication, and cooling are required during the grinding process; after the second grinding is completed, the grinding area needs to be cleaned to avoid residual particles affecting the roughness of the next grinding.

[0130] The third grinding step Q3: the grooving particle size is 1000-1500 mesh, and the grooving feed is 0.05mm; the third grinding requires fine-tuning of the surface, and cleaning, lubrication, and cooling are required during the grinding process; after the third grinding is completed, the grinding area needs to be cleaned to avoid residual particles affecting the roughness of the next grinding.

[0131] The fourth grinding step Q4: the grooving particle size is 1500-3000 mesh, and the grooving feed is 0.01mm; the fourth grinding step is to polish the surface to minimize the surface roughness.

[0132] Based on the same inventive concept, this embodiment provides a prism, which is a prism obtained using the prism processing method described above, and can be referred to... Figure 1 , Figure 2 , Figure 7 The diagram shows the structure of the prism.

[0133] Based on the same inventive concept, this embodiment provides a lens module, which includes a prism obtained using the prism processing method described above. (See also...) Figure 3The diagram shows the lens module architecture.

[0134] Since the electronic device described in this embodiment is an electronic device used to implement the information processing method in the embodiments of this application, those skilled in the art can understand the specific implementation methods and various variations of the electronic device in this embodiment based on the information processing method described in the embodiments of this application. Therefore, how the electronic device implements the method in the embodiments of this application will not be described in detail here. Any electronic device used by those skilled in the art to implement the information processing method in the embodiments of this application falls within the scope of protection of this application.

[0135] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0136] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A prism processing method, characterized in that, The method includes: A prism to be processed is provided, the prism to be processed having a target groove; the material of the prism to be processed is glass; The prism to be treated is immersed in a target acidic solution for a preset time to obtain a pretreated prism with a corrosion layer formed on its surface. The method for determining the preset time includes: determining the crack depth of the prism to be treated in the region where the target groove is located; determining the preset time based on the corrosion intensity of the target acidic solution and the crack depth; wherein, the corrosion intensity of the target acidic solution is the corrosion depth corresponding to different concentrations of target acidic solution at different times. The pretreated prism is removed, the corrosion layer is removed, and the target prism is obtained.

2. The method as described in claim 1, characterized in that, The provision of the prism to be processed includes: Provide the original prism; Based on the distribution area of ​​interfering light in the original prism, the target grooving parameters corresponding to the grooving of the original prism are determined; the target grooving parameters include the shape, size, and location of the grooving. The grooving particle size and grooving feed rate for each of the N grinding operations are determined based on the target grooving parameters; where N is a positive integer greater than or equal to 1. The original prism is grooved according to the corresponding grooving particle size and grooving feed amount for each grinding, to obtain the prism to be processed.

3. The method as described in claim 1, characterized in that, The removal of the corroded layer includes: The surface of the target groove of the prism to be processed is ground; The outer surface of the prism to be processed is finely ground and polished.

4. The method as described in claim 1, characterized in that, After obtaining the target prism, the method further includes: Detect whether the penetration rate of the target prism in the target groove exceeds a preset threshold; When the penetration rate of the target prism in the target groove exceeds the preset threshold, the outer surface of the target prism is ground until the penetration rate of the target prism in the target groove is less than the preset threshold.

5. The method as described in claim 1, characterized in that, After obtaining the target prism, the method further includes: A light-shielding material is coated inside the target groove of the target prism to obtain a semi-finished prism; The target type of colloid is filled into the target groove of the semi-finished prism to obtain the finished prism; The target type of colloid is a heat-curing colloid; the viscosity of the target type of colloid is 5000 mPa·s-25000 mPa·s.

6. The method as described in claim 1, characterized in that, The target acidic solution is any one of hydrofluoric acid, sulfuric acid, nitric acid, and phosphoric acid.

7. The method as described in claim 6, characterized in that, The concentration of the hydrofluoric acid is 20%-60%.

8. A prism, characterized in that, The prism includes a prism obtained by any one of the prism processing methods described in claims 1-7.

9. A lens module, characterized in that, The prism includes a prism obtained by any one of the prism processing methods described in claims 1-7.

Citation Information

Patent Citations

  • Glass lens processing method and mixed acid for processing glass lens

    CN104016577A

  • Light path folding prism, camera module and electronic equipment

    CN117270292A